Significance loss as the rhetoric of extreme ideologies: Evidence from the political and the terroristic context - Gabriele Di Cicco; Federico Contu; Laura Prislei; Michele J. Gelfand; Arie W. Kruglanski; Erica Molinario (Current Research in Ecological and Social Psychology)
Drawing on the Significance Quest Theory (Kruglanski et al., 2022), we used the Honor Dictionary (Gelfand et al., 2015) in a word frequency textual analysis (Pennebaker et al., 2007) to investigate extreme rhetoric. We thus conducted two studies. The first, investigating the political context, compared speeches of fascist dictator Benito Mussolini (1918–1945, N = 284) with those of democratic Presidents of the Italian Republic (1949–2006, N = 901). The second, focused on lone-actors terrorists, examined texts from the Extremist Manifesto Database (EMD, Grigoryan et al., 2023) and compared writings by terrorists driven by political ideologies (left & right-wing, ethno-nationalists, and anti-government, N = 65) with those of terrorists motivated by religious ideologies (N = 23). Notably, we hypothesized and found that, compared to democratic rhetoric, fascist rhetoric contained (a) more words expressing feelings of lost honor and (b) fewer words reflecting gaining honor. Moreover, as expected, we found that lone-actor religious terrorists' rhetoric, compared to lone-actor political terrorists, contained more words expressing feelings of lost honor and fewer words expressing honor gain. Notably, this is the first research to use the Honor Dictionary to linguistically measure the activation of the need for significance, demonstrating a strong correlation with the endorsement of extreme ideologies. Further, our research supports the hypothesis that extreme rhetoric reflects–and aims to induce–significance loss feelings.